Correction to EcoFlex: a multifunctional MoClo kit for E. coli synthetic biology. - Moore,SJ; Lai,H-E; Kelwick,RJR; Chee,SM; Bell,DJ; Polizzi,KM; Freemont,PS (ACS Synthetic Biology, 2020)
It has been brought to our attention that the original article contains a typographical error within Figure 1B, part ii. One of the 4-bp overhangs reads “GGAC” and should instead be “GTAC”, as is consistent throughout the original manuscript and deposited AddGene sequences.